2005
DOI: 10.1007/s00705-004-0473-x
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of H5 influenza viruses for ducks

Abstract: Four H5N1 highly pathogenic avian influenza (HPAI) viruses and an avirulent reassortant H5N1 virus were tested for their pathogenicity in domestic ducks. A/chicken/Yamaguchi/7/04 (H5N1) (Ck/Yamaguchi/04) isolated from a dead bird during the HPAI outbreak in Japan and A/duck/Yokohama/aq-10/03 (H5N1) (Dk/Yokohama/03) isolated from duck meat at a quarantine inspection for importation from China replicated in multiple organs including the brain of ducks. The ducks infected with Ck/Yamaguchi/04 did not show any cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
54
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(65 citation statements)
references
References 13 publications
9
54
2
Order By: Relevance
“…This may indicate that S and lk viruses were more virulent for ducks than those presented in the study of Sturm-Ramirez et al (2005). S and Y viruses in this study were found to have slightly higher virus replication in the gastrointestinal tract than in the respiratory tract in mallards and were excreted at slightly higher virus titres from the cloaca than the oropharynx, which indicated that both viruses were transmitted primarily via the oralÁfaecal route, consistent with previous studies (Shortridge et al, 1998;Chen et al, 2004;Kishida et al, 2005). More intriguingly, S virus was found to be present at higher levels of virus in nearly all viscera of infected ducks than Y virus, which may indicate that S virus possessed higher affinity to duck tissues than Y virus and indicated that S virus was more virulent than Y virus for ducks.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This may indicate that S and lk viruses were more virulent for ducks than those presented in the study of Sturm-Ramirez et al (2005). S and Y viruses in this study were found to have slightly higher virus replication in the gastrointestinal tract than in the respiratory tract in mallards and were excreted at slightly higher virus titres from the cloaca than the oropharynx, which indicated that both viruses were transmitted primarily via the oralÁfaecal route, consistent with previous studies (Shortridge et al, 1998;Chen et al, 2004;Kishida et al, 2005). More intriguingly, S virus was found to be present at higher levels of virus in nearly all viscera of infected ducks than Y virus, which may indicate that S virus possessed higher affinity to duck tissues than Y virus and indicated that S virus was more virulent than Y virus for ducks.…”
Section: Discussionsupporting
confidence: 91%
“…However, recent outbreaks of H5N1 in domestic ducks and wild aquatic birds indicated that this longstanding equilibrium between influenza virus and water fowl may have been disrupted. During the 2003 to 2005 H5N1 avian influenza outbreaks in Asia, domestic ducks were among the species affected clinically (Kishida et al, 2005;Liu et al, 2005;Zhou et al, 2006). In the present study, we showed that although the four H5N1 influenza viruses each had multiple basic amino acids at the HA cleavage site, and were highly pathogenic in chickens, they exhibited differing pathogenicity in mallards*with Y and hn viruses being of low pathogenicity in mallards, while S and lk isolates were highly pathogenic in this avian model.…”
Section: Discussionmentioning
confidence: 47%
“…A/chicken/Yamaguchi/7/04 (H5N1) (13,14) and A/chicken/aq-Y-55/01 (H9N2) (12) were used as HPAI and LPAI viruses, respectively. A/swine/Hokkaido/2/81 (H1N1), A/swine/ Miyagi/5/03 (H1N2), A/swine/Nakorn Pathom/02 (H3N2), and A/duck/Pennsylvania/10128/84 (H5N2) were used for the inoculation of miniature pigs.…”
mentioning
confidence: 99%
“…In the brain tissue of experimentally infected ducks, the virus concentration was 10 6.5 EID 50 in those that died showing brain involvement, and up to 10 3.6 EID 50 in ducks without clinical signs of the disease (Kishida et al, 2005). The virus concentration in the brain tissue of the examined swan was estimated by us 10 5.0 EID 50 and this made us assume that, at that virus concentration, the birds' brains may have been affected.…”
Section: Discussionmentioning
confidence: 93%
“…(Lee et al, 2005;Kishida et al, 2005;Swayne, 2006;Zhou et al, 2006). By monitoring the time dynamics of virus excretion from the digestive or respiratory systems and assessing its concentration, risk factors for the spread of infection to other birds can be estimated.…”
Section: Discussionmentioning
confidence: 99%